INTRA VITREOUS BEVACIZUMAB VERSUS OBSERVATION IN ACUTE CENTRAL SEROUS CHORIORETINOPATHY. - Bassam Mubarik; Ghulam Murtaza; Samra Naseem (Journal of University Medical & Dental College, 2018)
ABSTRACT: OBJECTIVE: To compare the eﬃcacy of intravitreal bevacizumab for absorption of sub-retinal ﬂuid in central serus chorio retinopathy from observation alone. ABSTRACT: It was a retrospective study of 34 patients with acute central serous chorioretinopathy. Patients were divided in two groups. Group A of 17 patients with anti VEGF treatment and group B of 17 patients with observation alone. Central foveal thickness and resolution of sub retinal ﬂuid on OCT were assessed to determine the resolution of central serous retinopathy. RESULTS: Resolution of sub retinal ﬂuid was observed in all patients, in anti VEGF group A as well as in group B patients at 12 months. CONCLUSION: In terms of resolution of sub retinal ﬂuid anti VEGF as well as observation alone had similar therapeutic eﬀects in acute central serous chorioretinopathy.